An Algorithm for Stabilization of Fractional-Order Time Delay Systems Using Fractional-Order PID Controllers - Hamamci, S.E. (IEEE transactions on automatic control, 2007)
This technical note presents a solution to the problem of stabilizing a given fractional-order system with time delay using fractional-order Pl lambda D mu controllers. It is based on determining a set of global stability regions in the (k p , K i , K d )-space corresponding to the fractional orders lambda and mu in the range of (0, 2) and then choosing the biggest global stability region in this set. This method can be also used to find the set of stabilizing controllers that guarantees prespecified gain and phase margin requirements. The algorithm is simple and has reliable result which is illustrated by an example, and, hence, is practically useful in the analysis and design of fractional-order control systems.